Thermal and dielectric properties of flexible polyimide nanocomposites with functionalized nanodiamond and silver nanoparticles - BİRTANE, HATİCE; MADAKBAŞ, SEYFULLAH; ESMER, KADİR; KAHRAMAN, MEMET VEZİR (My University, 2023)
In the present study, amine groups were first modified to diamond and silver nanoparticles using APTMS to improve their homogeneous dispersion and compatibility in polyamic acid. Flexible polyimide nanocomposite films were successfully prepared by adding modified nanodiamond and silver nanoparticles to 4,4 \"-(1,3-phenylenedioxy) dianiline and benzophenone-3,3 \",4,4 \"-tetracarboxylic dianhydrides with different proportions. The effects of added amine-modified nanoparticles on dielectric constant and thermal stability were investigated. With SEM analysis, nanoparticles were homogeneously distributed on the polyimide surface and the presence of Si atom resulting from APTMS modification is clearly seen with the SEM-EDAX results. Considering the thermal resistance, the maximum decomposition temperature of the nano particle-free PI film was found to be 501 degrees C, while the thermal decomposition temperatures of the PI nanocomposite film that contains 1% m-Ag and the PI film that contains 5% m-ND, 502 degrees C and 505 degrees C, respectively. Also, it was seen that the dielectric constants of the prepared nanocomposite films that contain m-Ag NP decrease with increasing m-Ag NP ratio, and the dielectric constants of the films that contain m-ND increase with increasing m-ND ratio.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; POLİMER BİLİMİ; Temel Bilimler (SCI); POLYMER SCIENCE; CHEMISTRY; Natural Sciences (SCI); Polimerler ve Plastikler; Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Polymers and Plastics; Chemistry (miscellaneous); General Chemistry; Physical Sciences; Flexible polyimide films; Ag nanoparticles; Nanodiamond particles; Dielectric properties; Thermal properties; POLYMER; COMPOSITES; FILMS; CONDUCTIVITY; DISPERSION